Politik Santri: Pemikiran dan Aksi (Studi Kasus Pondok Pesantren Tebuireng): Santri Politics: Thought and Action (A Case Study of Tebuireng Islamic Boarding School) - Fanani, Zainul (LP2M UIN KH.Achmad Siddiq Jember, 2010)
This research is aimed at understanding the political thought and action of Tebuireng's santri from their own perspectives. Based on the emic perspective, the analysis unit is a social phenomenon that can be observed. This research focuses on understanding the world of santri themselves. The research has two assumptions: first, the choice and political tendencies of Tebuireng's santri are not subjected to critical